Adrenocortical carcinoma classified as benign: the limitations of washout values - P S Yap; S Philip; A J Graveling; D McAteer; S Aspinall; P Abraham (Endocrinology, Diabetes & Metabolism Case Reports)
The new European Society of Endocrinology guidelines on the management of adrenal incidentalomas suggest discussion in a multidisciplinary meeting and consideration of additional imaging for homogenous lesions with a density >20 Hounsfield units (HU) and size <4 cm. We report a case of a 29-year-old woman who presented with benign-looking lesion on CT adrenals based on washout values, which was diagnosed as malignant on subsequent imaging. Initial hormonal work-up was normal. Two years later, the lesion had grown to 17 × 11 cm. Repeat hormonal work-up showed a raised urinary steroid profile and androstenedione along with an abnormal overnight dexamethasone suppression test. Our case report highlights a lesion being classified as benign based on washout recommendations subsequently diagnosed as adrenocortical carcinoma. We have reviewed our current clinical cohort and literature to assess the impact of the updated European guidelines on our practice, with particular reference to the use of HU. Learning points: For the assessment of adrenal incidentalomas, CT washout values have limitations and should be interpreted with caution. Additional imaging may be required for lesions above 10 HU and this can vary according to centre expertise and availability. An adrenal lesion with a high HU value warrants follow-up imaging even if post-contrast washout values favour an adenoma. Adrenal incidentaloma are less common in younger patients, but are more likely to be clinically significant and/or malignant, so clinicians should have a lower threshold for surgery or interval imaging in indeterminate cases.